2009
DOI: 10.1029/2008gl036670
|View full text |Cite
|
Sign up to set email alerts
|

Daytime low‐altitude quasi‐periodic echoes at Gadanki: Understanding of their generation mechanism in the light of their Doppler characteristics

Abstract: In this paper, we investigate the genesis of low‐altitude quasi‐periodic (LQP) E region echoes observed during daytime by the Gadanki radar. We show that such echoes reflect much wider Doppler spectra compared to that of typical daytime low‐altitude E‐region echoes. Further, the Doppler spread resembles that of meteor induced spread echoes. Considering that the meteor spread echoes are generated by the gradient drift instability on the sharp density gradient associated with the plasma trail, we invoke plasma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Another relevant aspect and frequently observed phenomena is the observation of VHF (MST) radar echoes from the magnetic filed‐aligned irregularities (FAI) in the altitude region of 88–100 km [ Krishna Murthy et al , 1998; Patra et al , 2006] over this station. Although their structures were observed to have features of tidal ion layer commonly observed and reported for Arecibo [e.g., Mathews , 1998], radar echoes from E region FAI extending down to altitude as low as 88 km were shown to be puzzling [ Patra et al , 2006, 2009]. Patra et al [2009] provided a detailed analysis on the genesis of ultralow altitude echoes and advocated that they are generated by weak Kelvin‐Helmholtz instability (KHI).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect and frequently observed phenomena is the observation of VHF (MST) radar echoes from the magnetic filed‐aligned irregularities (FAI) in the altitude region of 88–100 km [ Krishna Murthy et al , 1998; Patra et al , 2006] over this station. Although their structures were observed to have features of tidal ion layer commonly observed and reported for Arecibo [e.g., Mathews , 1998], radar echoes from E region FAI extending down to altitude as low as 88 km were shown to be puzzling [ Patra et al , 2006, 2009]. Patra et al [2009] provided a detailed analysis on the genesis of ultralow altitude echoes and advocated that they are generated by weak Kelvin‐Helmholtz instability (KHI).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although their structures were observed to have features of tidal ion layer commonly observed and reported for Arecibo [e.g., Mathews , 1998], radar echoes from E region FAI extending down to altitude as low as 88 km were shown to be puzzling [ Patra et al , 2006, 2009]. Patra et al [2009] provided a detailed analysis on the genesis of ultralow altitude echoes and advocated that they are generated by weak Kelvin‐Helmholtz instability (KHI). Thus, it is prudent to consider the temperature structures, since they play an important role on the excitation of KHI.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Driven by KHI, E S structure is destabilized by collision between plasma and neutral particles, and then evolves into the K‐H structure, resulting in QP echoes in radar maps. Correlative studies have been performed by Sripathi et al (2003) and Patra et al (2009). A 2‐D numerical model of the evolution of E S in KHI modulation is shown in Figure 9 (Bernhardt, 2002).…”
Section: E Region Irregularitymentioning
confidence: 99%
“…Coming to the low-latitude observations of E-region irregularities, investigations suggested that the low latitude Eregion irregularities are closely linked to the tidal and gravity wave dynamics (e.g., Patra et al, 2005Patra et al, , 2009Venkateswara Rao et al, 2008). Patra et al (2009), based on their investigation, surmised that metallic ions must be playing a crucial role in the layer formation and thus in the instability process.…”
Section: Introductionmentioning
confidence: 99%
“…Patra et al (2009), based on their investigation, surmised that metallic ions must be playing a crucial role in the layer formation and thus in the instability process. No experimental proof, however, could be provided so far.…”
Section: Introductionmentioning
confidence: 99%